ANALYSIS OF THE FACTORS WHICH INFLUENCE THE PERFORMANCE OF REGIONAL FINANCIAL PERSONNELS IN THE SAMOSIR DISTRICT ADMINISTRATION WITH WELFARE ALLOWANCE AS THE MODERATING VARIABLE - Adinita, Sherli (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of Regional Government Accounting System Understanding , competency, financial administration, and regional government property management on the performance of regional financial personnel simultaneously and partially and to examine and analyze welfare allowance in moderating the correlation of regional government accounting system, competency, financial administration, and regional government property management with the performance of financial personnel. The research used associative causal quantitative method. It also used survey approach by distributing questionnaires to regional financial personnel in the Samosir District Government. The population was 151 financial personnel at 38 SKPDs, and the samples were taken by using census sampling technique. The data were analyzed by using multiple linear regression analysis and residual test. The result of the research showed that simultaneously regional government accounting system, competency, financial administration, and regional government property management had significant influence on the performance of financial personnel. Partially, regional government accounting system and regional government property management had positive and significant influence on the performance of financial personnel. Welfare allowance was able to mediate the correlation of regional government accounting system, competency, financial administration, and regional government property management with the performance of financial personnel.